The Role of Mediators and The Legal Force of Recommendation in the Settlement of Industrial Relations Disputes - Taufik Hidayat; Darwati Darwati (Asian Journal of Social and Humanities, 2026)
Industrial relations disputes remain a significant challenge in Indonesia’s employment landscape, often arising from disagreements over rights, interests, termination of employment, or conflicts among labor unions. Although the legal framework prioritizes dispute resolution through deliberation and consensus, with bipartite negotiations serving as the primary mechanism, mediation plays a crucial role when such negotiations fail. This study analyzed the role of mediators and the legal implications of mediator recommendations, both normatively and empirically, while evaluating the extent to which existing legal provisions align with the principles of justice and the judicial ideals of simplicity, speed, and low cost. Employing a normative juridical research method with statutory and conceptual approaches, this study examined Law Number 2 of 2004 concerning the Settlement of Industrial Relations Disputes, labor regulations, and Constitutional Court Decision Number 68/PUU-XIII/2015. The findings revealed that although mediators play a significant role in facilitating dispute resolution by providing legal clarification and proposing equitable solutions, their recommendations lack binding legal force, thereby reducing their effectiveness and creating legal uncertainty. This condition may disproportionately disadvantage workers, who are generally in weaker socio-economic positions. The study recommends legal reform to strengthen the enforceability of mediator recommendations, including the establishment of statutory time limits and the potential granting of binding force under certain conditions, to enhance legal certainty, efficiency, and fairness in industrial dispute resolution.